Establishment and Application of a Dual-Labeling Time-Resolved Fluorescence Immunoassay Method for Simultaneous Detection of the Troponin I-C Complex and Full-Size-Troponin I - Huang, Biao; Wu, Jian; Chen, Hao; Zhang, Li; Zhou, Xiumei; Wu, Qingqing; Li, Ting; Wang, Yigang; Xia, Penguo; Dai, Yaping; Kai, Guoyin; Liu, Pengfei; et al. (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND: The measurement of cardiac troponin I (cTnI) is widely used for diagnosis of acute myocardial infarction (AMI). The significance of undegraded full-size-cTnI levels is still not well understood. In this study, we have established a novel dual-labelling time-resolved fluorescence immunoassay (TRFIA) technique that simultaneously detects the cTnI-C complex and full-size-cTnI, allowing us to explore the clinical value of full-size-cTnI determination. METHODS: An antibody against the region of cTnI protected by endogenous cTnC is coupled to the magnetic beads as a solid-phase antibody for capturing all cTnI, an antibody against the cTnI-C complex labeled Eu3+ was used to detect the cTnI-C complex, and an antibody labeled Sm3+ near the C-terminal of cTnI was used to detect full-size-cTnI. Through dual-labeled TRFIA, cTnI-C complex, full-size-cTnI and the ratio of full-size-cTnI/ cTnI-C can be detected simultaneously. The dual-labeled TRFIA was used to detect samples, comparing the ratio of full-size-cTnI/cTnI-C in serum collected at different times during treatment. RESULTS: The sensitivity of cTnI-C-TRFIA complex was 0.02 ng/mL, The correlation coefficient between cTnI-C-TRFIA and commercial cTnI-CLIA methods was R2=0.8887. The sensitivity of full-size-cTnI-TRFIA was 0.04 ng/mL, The correlation coefficient between full-size-cTnI-TRFIA and commercial cTnI-CLIA methods was R2=0.7247. The data of continuously monitored patients indicated that combined analysis of the cTnI concentration and full-size-cTnI/cTnI-C ratio allows for earlier prognosis than that afforded by cTnI concentration detection alone CONCLUSIONS: The dual-labeled full-size-cTnI/ cTnI-C-TRFIA is helpful to determine the length of time of chest pain before admission and the degree of continuous release of cTnI in the myocardium.